Digital Culture and Digital Library - (:unkn) unknown (TURKISH LIBRARIANS ASSOC, 2016)
In this study; digital culture and digital library which have a vital connection with each other are examined together. The content of the research consists of the interaction of culture, information, digital culture, intellectual technologies, and digital library concepts. The study is an entry work to integrity of digital culture and digital library theories and aims to expand the symmetry. The purpose of the study is to emphasize the relation between the digital culture and digital library theories acting intersection of the subjects that are examined. Also the perspective of the study is based on examining the literature and analytical evaluation in both studies (digital culture and digital library). Within this context, the methodology of the study is essentially descriptive and has an attribute for the transmission and synthesis of distributed findings produced in the field of the research. According to the findings of the study results, digital culture is an inclusive term that describes the effects of intellectual technologies in the field of information and communication. Information becomes energy and the spectrum of the information is expanding in the vertical rise through the digital culture. In this context, the digital library appears as a new living space of a new environment. In essence, the digital library is information-oriented; has intellectual technology support and digital platform; is in a digital format; combines information resources and tools in relationship/communication/cooperation by connectedness, and also it is the dynamic face of the digital culture in time and space independence. Resolved with the study is that the digital libraries are active and effective in the formation of global knowing and/or mass wisdom in the process of digital culture.
Keywords: Culture; erudition and deep knowledge; digital culture; intellectual technology; digital library